Destination Branding in the Context of K-Pop Culture (Korean Wave) in South Korean Tourism Market with Chinese Customers - ZHAO, YIFANG (2015)
The tourism industry is recognized as a national strategic force due to its economic rewards. Occupying a superior position in the global tourism market is important as the increasing competitiveness among countries. Thus managers of tourism industries tend to adopt branding strategies in order to attract more tourists and foreign direct investment. This paper aims to explore the strategies of branding Korean tourism from the perspective of customer, organization, and destination, with the purpose to position Korea as an appealing country in the mind of public. This paper analyse the characteristics of tourism product, consumer behaviour in tourism and theoretical models of brand-building to investigate the relevant factors that branding Korea as a tourism destination. This paper adopts brand building model to evaluate how elaborately the brand identity is from the following three perspectives: environment and competitor analysis; consumer, destination, and organization analysis; and brand vision. The Korean tourism brand includes what Korean tourism aspires to be, a unique set of brand associations, and brand awareness to build as much brand equity as possible. This paper also discusses the strategies for communicating and aligning the brand position, while building a loyal relationship with customers through an expanded marketing mix.